DESMITIFICANDO A LA DEEP WEB A TRAVÉS DE UN FUGAZ VIAJE POR LA DARK WEB - John Alexander Rico Franco (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2021)
At the moment when topics related to the Deep Web and the darkNets are treated, the imagination of the one who doesn’tknow it’s reality, is projected towards a gloomy environment of the Internet, with the setting of a CiberPunk anime film ofthe nineties; activity that is completely logical and normal, because in search of covering the gaps in knowledge, peoplerefer to folk and fictional stories from multiple sources, in particular, television series, mystery novels, among otherproducts from science fiction; references that have a lot of exaggeration and rarely a bit of reality, which increases themyths concerning the Deep and Dark Webs; this is because most of the people take these fictitious references as realities,because these sectors of cyberspace are still a myth unexplored by the most of their casual navigators.This is why we seek to demystify the conception of the Deep Web and the darkNets and give clarity to a very interestingand dangerous online ecosystem at the same time, because in this mythical sector of cyberspace you can find largevolumes of useful information but also allows the free management of criminal commercial services. To achieve thisgoal, the present document has been segmented into four primary sectors: the first one is a basic introduction of what is cyberspace and what are it’s primary sectors, and then proceed to present the fundamentals to know the deployment ofthe Deep Web and the darkNets, and with these foundations already go on to present a secure browsing session throughthe darkNet TOR with the help of a virtualized protected navigation environment, that will help to present some of themost common criminal services of the Dark Web, in order to close this article with a final conclusions about the realityof cyberspace, its unknown areas and the dangers that are hosted there.